2017
DOI: 10.1515/aoa-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Types of Combined Measures, STI and U50, for Predicting Speech Intelligibility in Classrooms

Abstract: The present study reports on the speech intelligibility as measured by speech transmission index (STI) and useful-to-detrimental sound ratios (U50) in university classrooms. Acoustic measurements were made in 12 quietly occupied university classrooms. The measured impulse responses of the classrooms were used to determine the modulation transfer function, m(F ), for the STI calculation according to IEC 60268-16. U50 values were determined from both signal-to-noise ratios (SNR) and C50 values. The mean STI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…Setting a fixed source-receiver distance of 1.25 m, and testing two SNRs (mean −8.5 and −4.5 dB), Picou et al (2019) found no effect of reverberation on listening effort in children. Based on the data reported in the study and the formulas in Long (2014) and Choi (2017), we can estimate the value of U 50 for their experimental conditions. For an SNR of −8.5 dB, U 50 was −10.5 dB for the short and −10.3 dB for the moderate reverberation times; for an SNR of −4.5 dB, it was −6.1 and −6.5 dB, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Setting a fixed source-receiver distance of 1.25 m, and testing two SNRs (mean −8.5 and −4.5 dB), Picou et al (2019) found no effect of reverberation on listening effort in children. Based on the data reported in the study and the formulas in Long (2014) and Choi (2017), we can estimate the value of U 50 for their experimental conditions. For an SNR of −8.5 dB, U 50 was −10.5 dB for the short and −10.3 dB for the moderate reverberation times; for an SNR of −4.5 dB, it was −6.1 and −6.5 dB, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…where "r h " is the reverberation distance where the energy densities of the reflected and direct sounds become equal; "r" is the source-receiver distance; "RT" is the reverberation time; SNR is the signal-to-noise ratio at "r." Table 2 indicates the octave band U 50 (125-8000 Hz) values for the classroom under quiet and noisy conditions. The average U 50 values calculated as a frequency-weighted sum 23 change by an order of nearly 2 dB across the two conditions. The influence of the presence of noise apart from reverberation is seen across all frequency bands, with the 1-kHz U 50 value ranging between −1.05 and −5.7 dB for quiet to noisy conditions, respectively.…”
Section: Room Acoustic Measuresmentioning
confidence: 96%
“…Frequency weightings as per the method used by Choi 23 were used to derive the octave band U 50 values by averaging the octave band values from 125 to 4000 Hz, considering that this range of octave band frequencies is home to all the vowel sounds and the mean U 50 was evaluated as a frequency-weighted sum. The octave band U 50 value evaluated at the center of the classroom was considered.…”
Section: Room Acoustic Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Distintos estudios evidencian la necesidad de mejoras en la acústica de las aulas de clase dado los niveles actuales de los parámetros acústicos en comparación con los estándares a nivel mundial [39,40,41,42,43,44,45,46,47,48,49,50], razón por la cual el conocimiento de las medidas de mejoramiento anteriormente mencionadas sería útil para aumentar los niveles de calidad de la acústica en las instituciones educativas.…”
Section: Medidas De Mejoramientounclassified